2007
DOI: 10.1016/j.ejcts.2006.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative outcome of patients undergoing lung resection presenting with new-onset atrial fibrillation managed by amiodarone or diltiazem

Abstract: Postoperative outcome of patients undergoing lung surgery with new onset of AF resulted as being significantly complicated by AF recurrence in the case of an associated respiratory complication. The pharmacological strategies tested during this pilot study led to no differences in the postoperative course of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 22 publications
0
34
0
1
Order By: Relevance
“…Proposed precipitating factors for postoperative supraventricular arrhythmias in patients recovering from thoracic surgery are pulmonary gas exchange disturbances [25], systemic inflammation [25] and autonomic denervation inflicted by anatomic pulmonary resection [26]. In support of a multifactorial mechanism is a recent study, which demonstrated that atrial fibrillation occurred in 12% of patients undergoing VATS and 16% of patients undergoing thoracotomy, a nonsignificant difference [26].…”
Section: Thoracic Surgerymentioning
confidence: 96%
See 1 more Smart Citation
“…Proposed precipitating factors for postoperative supraventricular arrhythmias in patients recovering from thoracic surgery are pulmonary gas exchange disturbances [25], systemic inflammation [25] and autonomic denervation inflicted by anatomic pulmonary resection [26]. In support of a multifactorial mechanism is a recent study, which demonstrated that atrial fibrillation occurred in 12% of patients undergoing VATS and 16% of patients undergoing thoracotomy, a nonsignificant difference [26].…”
Section: Thoracic Surgerymentioning
confidence: 96%
“…The most robust risk factors for increased incidence of postoperative atrial fibrillation that were most consistently reported were advanced age and extent of pulmonary resection (with decreasing incidence: pneumonectomy vs. lobectomy vs. VATS) [24,32]. Other factors included male gender, preoperative arrhythmias, peripheral vascular disease, mediastinal lymph node dissection, need for repeated thoracotomy or right sided procedure, history of diabetes mellitus, hypertension, chronic obstructive pulmonary disease (COPD), preoperative pulmonary functional status, postoperative respiratory complication, chylothorax, history of congestive heart failure, coronary artery disease, beta-blocker ingestion, previous cardiopulmonary disease and anesthetic technique [24,25,[28][29][30][31]33]. Hence, the ability to accurately identify patients at high risk for atrial fibrillation is limited.…”
Section: Thoracic Surgerymentioning
confidence: 99%
“…Drugs and drug dosages used for rate control are described in Table 4. The rationales for such recommendations are based on available data from observational and small prospective randomized studies that have demonstrated that most cases of new-onset POAF are restored to sinus rhythm in the first 24 hours, regardless of what treatment strategies were used [137,138,141,142]. Among commonly used rate control agents are betablockers (esmolol and metoprolol), non-dihydropyridine calcium-channel blockers (diltiazem and verapamil), amiodarone, and digoxin.…”
Section: Rate Control Strategymentioning
confidence: 98%
“…POAF is associated with longer intensive care unit and hospital stays, increased morbidity (including strokes/new central neurological events; with incidence of 1.3–1.7 %; [2], [10], [26]–[29] and mortality (up to 5.6–7.5%; RR:1.7–3.4; [5], [26], [28]), as well as higher resource utilization [2], [6], [10], [26]–[30]. …”
Section: Epidemiology Of Perioperative Atrial Fibrillation and Fluttementioning
confidence: 99%
“…Patients taking β-blockers prior to thoracic surgery should continue them in the postoperative period to avoid β-blockade withdrawal [3], [26], [29], [101]–[106]. (LOE A)…”
Section: Recommendations and Reasoningmentioning
confidence: 99%